Sprite Durations Measured With a Neuromorphic Sensor - B. Smith; M. G. McHarg; C. L. daSilva; R. G. Sonnenfeld; J. Koile; A. F. R. Leal; I. R. Jones (Geophysical Research Letters)
Abstract Neuromorphic sensors have inherently‐fast speeds and low data rates, which potentially make them ideal for the observation of transient sources, such as lightning and sprites. Particularly, for remote observations. In this article, we report the first observations of sprites from the ground with a neuromorphic sensor. These observations are accompanied by measurements with established instruments such as low‐light level and high‐frame rate cameras. We determine that neuromorphic sensors can capture sprites and determine their duration to an accuracy of roughly 6 ms. Average sprite durations were found to be 55 ms within our data set. We have also ascertained that sprites may be too dim for the neuromorphic sensors to resolve the internal spatiotemporal dynamics, at least without the aid of intensifiers.